The Influence of Green Credit, Operational Efficiency, and Green Finance Policy on Banking Profitability in Indonesia in 2020-2024 - Elgin Nathaniel; Nurhana Dhea Parlina (Interdisciplinary Social Studies, 2026)
This study aims to analyze the influence of Green Credit, operational efficiency as measured by the BOPO ratio, and Green Finance Policy on the profitability of conventional banking in Indonesia for the period 2020–2024. The study used a quantitative approach with secondary data in the form of annual reports and sustainability reports of banks listed on the Indonesia Stock Exchange. The sample was selected through the purposive sampling technique and produced 9 banks with a total of 45 observations. The analysis was carried out using panel data regression accompanied by model selection tests, classical assumption tests, and partial and simultaneous hypothesis tests. The results of the study show that partially Green Credit and Green Finance Policy do not have a significant effect on profitability (ROA), although both have a positive relationship direction. On the other hand, operational efficiency (BOPO) has a negative and significant effect on profitability, which confirms that controlling operating costs is the main factor determining the bank's profit performance. Simultaneously, the three independent variables had a significant effect on ROA with an Adjusted R² value of 0.853555, indicating that the model was able to explain 85.36% of the variation in profitability. These findings indicate that the implementation of sustainable finance has not had a direct impact on short-term profits, but has the potential to provide long-term benefits when accompanied by good operational efficiency.